Impacts of environmental stress on resistance and resilience of algal‐associated bacterial communities. Issue 21 (6th October 2021) - Morrissey, Kathryn Lee; Iveša, Ljiljana; Delva, Soria; D'Hondt, Sofie; Willems, Anne; De Clerck, Olivier
Abstract: Algal‐associated bacteria are fundamental to the ecological success of marine green macroalgae such as Caulerpa . The resistance and resilience of algal‐associated microbiota to environmental stress can promote algal health and genetic adaptation to changing environments. The composition of bacterial communities has been shown to be unique to algal morphological niches. Therefore, the level of response to various environmental perturbations may in fact be different for each niche‐specific community. Factorial in situ experiments were set up to investigate the effect of nutrient enrichment and temperature stress on the bacterial communities associated with Caulerpa cylindracea . Bacteria were characterized using the 16S rRNA gene, and the community compositions were compared between different parts of the algal thallus (endo‐, epi‐, and rhizomicrobiome). Resistance and resilience were calculated to further understand the changes of microbial composition in response to perturbations. The results of this study provide evidence that nutrient enrichment has a significant influence on the taxonomic and functional structure of the epimicrobiota, with a low community resistance index observed for both. Temperature and nutrient stress had a significant effect on the rhizomicrobiota taxonomic composition, exhibiting the lowest overall resistance to change. The functional performance of the rhizomicrobiota had low resilience to the combination of stressors, indicating potential additive effects. Interestingly, the endomicrobiota had the highest overall resistance, yet the lowest overall resilience to environmental stress. This further contributes to our understanding of algal microbiome dynamics in response to environmental changes. Abstract : The resistance and resilience of algal‐associated microbiota to environmental stress can promote algal health and genetic adaptation to changing environments. Bacteria associated with separate morphological niches along the thallus of Caulerpa cylindracea differed significantly in response to environmental perturbations, further contributing to our understanding of algal microbiome dynamics.